Capturing Inherent Variability in Solar PV Energy through Realistic Estimates: A Case Study for the State of Minnesota - Vaidyanathan, Dr. Mouli (Distributed Generation & Alternative Energy Journal, 2013)
Solar photovoltaic (PV) deployment in the United States and the world is gaining accelerated momentum. It is very important for the solar PV industry standards to be realistic in its energy production estimates. The model of choice for most solar PV installers, enthusiasts and owners is the use of National Renewable Energy Laboratory (NREL) PV Watts’ simulation program. Through systematic analysis of multiple installations in the State of Minnesota, real data are analyzed and compared to the PV Watt’s simulated results. It has been determined through this analysis that PV Watts is aggressive, unattainable and misleads the public in its energy estimates for the State of Minnesota. It has also been discussed that to obtain more realistic solar PV en- ergy estimates, one must use of range of production rather than just one value. Giving one value for solar PV energy estimates has the tendency to mislead because a low value estimate would make solar PV unattract- ive and a high value estimate will not be consistently attainable. Using an average PV energy production is also deceptive, since by definition, half of the values are below and half are above the average. So, it’s im- perative to understand the statistical nature of available solar energy at any given time, which varies by the hour of the day and the season in the year. Thus, through systematic analysis, a range of solar PV energy production estimate for the State of Minnesota is being presented which is different and more accurate than NREL’s PV Watts. Other significant results summarized are the correlation between energy production and precipitation, effects of tilt angles on energy pro- duction, summer and winter energy production, equipment related en- ergy production and string and microinverter effects on energy produc- tion.